International competitiveness of national economy of Poland. (Economic and Political Thought, 2017)
The article presents the concept and types of international competitiveness.It shows current international position and competitive capacity of thePolish economy. It presents reference made to other countries. Indicators ofand reports on international competitiveness are used in the analysis.